Trojan Horse or Useful Helper? A Relationship Perspective on Artificial Intelligence Assistants with Humanlike Features - Uysal, Ertugrul Behlül; Alavi, Sascha; Bezençon, Valéry (My University, 2022)
Artificial intelligence assistants (AIAs) such as Alexa are prevalent in consumers’ home. Due to their powerful artificial intelligence, consumers may perceive that AIAs have a mind of their own, that is, they are anthropomorphizing them. Past marketing research points to beneficial effects of AIA anthropomorphism for consumers and companies, while potential harmful effects are less explored. To examine both beneficial and costly effects, the paper adopts a relationship perspective. Indeed, consumers spend large amounts of time with their AIA, potentially developing a relationship over time that builds on an exchange of benefits and (psychological) costs. A field study and a field experiment with AIA users show that AIA anthropomorphism may threaten users’ identity, which disempowers them, creates data privacy concerns and ultimately undermines their well-being. These harmful effects particularly emerge in close, long relationships. The field experiment uncovers three empowering interventions, which attenuate harmful effects of AIA anthropomorphism in relationships with consumers.
, 2022
Keywords: Artificial Intelligence Assistants; Anthropomorphism; Privacy of Personal Data; Social Exchange; Smart Personal Assistants; Empowerment; Consumer Well-being